Spiritualitas, Koping dan Gangguan Tidur pada Pasien Gagal Ginjal Kronik - Erna Melastuti; Nur Lu’luatul Maknunah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Chronic renal failure patients undergoing hemodialysis often experience sleep problems. This condition can affect the patient's quality of life physically and mentally. This study examined the relationship between the level of spirituality, coping mechanisms, and sleep disturbances in chronic renal failure patients undergoing hemodialysis. Psychological factors such as the level of spirituality and coping mechanisms can affect patients' adaptation to stress due to chronic illness, including sleep disturbances. Using a cross-sectional design, this study involved several patients who were in the hemodialysis room of the hospital. The purposive sampling method was used to conduct this study on seventy samples. Data processing was done with the chisquare test. The results showed that the sign value of 0.034 < 0.005 and 0.038 < 0.05, which indicates that H0 is rejected and Ha is accepted. There is a relationship between age, gender, level of spirituality, coping mechanisms, sleep disorders in chronic renal failure patients undergoing hemodialysis. In addition, adaptive coping mechanisms were also found to have a positive correlation with good sleep quality. This study concludes that increasing spirituality with adaptive coping mechanisms can contribute to the improvement of sleep quality in chronic renal failure (CKD) patients undergoing hemodialysis.